The Generation and Identity of Human Myeloid-Derived Suppressor Cells - Bergenfelz, Caroline; Leandersson, Karin (Frontiers in Oncology, 2020)
Myeloid-derived suppressor cells (MDSCs) are cells of myeloid lineage with a potent immunosuppressive capacity. They are present in cancer patients as well as in patients with severe inflammatory conditions and infections. MDSCs exist as two main subtypes, the granulocytic (G-MDSCs) and the monocytic (Mo-MDSCs) type, as defined by their surface phenotype and functions. While the functions of MDSCs have been investigated in depth, the origin of human MDSCs is less characterized and even controversial. In this review we recapitulate theories on how MDSCs are generated in mice, and whether this knowledge is translatable into human MDSC biology, as well as on problems of defining MDSCs by their immature cell surface phenotype in relation to the plasticity of myeloid cells. Finally, the challenge of pharmacological targeting of MDSCs in the future is envisioned.